Evident but context‐dependent mortality of fish passing hydroelectric turbines - Johannes Radinger; Ruben van Treeck; Christian Wolter (Conservation Biology, 2022)
Globally, policies aiming for conservation of species, free‐flowing rivers, and promotion of hydroelectricity as renewable energy and as a means to decarbonize energy systems generate trade‐offs between protecting freshwater fauna and development of hydropower. Hydroelectric turbines put fish at risk of severe injury during passage. Therefore, comprehensive, reliable analyses of turbine‐induced fish mortality are pivotal to support an informed debate on the sustainability of hydropower (i.e., how much a society is willing to pay in terms of costs incurred on rivers and their biota). We compiled and examined a comprehensive, global data set of turbine fish‐mortality assessments involving >275,000 individual fish of 75 species to estimate mortality across turbine types and fish species. Average fish mortality from hydroelectric turbines was 22.3% (95% CI 17.5–26.7%) when accounting for common uncertainties related to empirical estimates (e.g., handling‐ or catch‐related effects). Mortality estimates were highly variable among and within different turbine types, study methods, and taxa. Technical configurations of hydroelectric turbines that successfully reduce fish mortality and fish‐protective hydropower operation as a global standard could balance the need for renewable energy with protection of fish biodiversity.